Current Insights in Cutaneous Lupus Erythematosus Immunopathogenesis - Garelli, Colton J.; Refat, Maggi Ahmed; Nanaware, Padma P.; Ramirez-Ortiz, Zaida G.; Rashighi, Mehdi; Richmond, Jillian M. (Frontiers in Immunology, 2020)
Cutaneous Lupus Erythematosus (CLE) is a clinically diverse group of autoimmune skin diseases with shared histological features of interface dermatitis and autoantibodies deposited at the dermal-epidermal junction. Various genetic and environmental triggers of CLE promote infiltration of T cells, B cells, neutrophils, antigen presenting cells and NK cells into lesional skin. In this mini-review, we will discuss the clinical features of CLE, insights into CLE immunopathogenesis, and novel treatment approaches.